Pengaruh Pemberian Kompres Panas untuk Mengurangi Nyeri Persalinan pada Kala I Fase Aktif di BPM Susi Hersaptiti Desa Kalikebo, Trucuk Klaten, Jawa Tengah Tahun 2014 - Fatimah Sari; Nova Wijanarko; Mustika Pramestyani (Journal of Health (JoH), 2015)
Background: Mothers who give birth often experience pain and no pain will rarely cause anxiety, muscles become spastic, rigid, narrow birth canal and less relaxation. It also can cause fatigue in a decrease uterine contractions. The number of women who want to give birth with the birth process that takes place without pain, the various efforts undertaken to reduce pain in childbirth,both pharmacological and non-pharmacological. One alternative non-pharmacological administration of hot compress on the back. Objective: Knowing the effect of hot compress compresses to reduce pain in active phase of the first stage of labor on Susie Hersaptiti BPM. Methods: The study was a Quasi Experiment. With one group pre-test post-test. Respondents in this study were all women giving birth in the active phase of the first stage in BPM Susi Hersaptiti the number of subjects 10 mothers, who were taken by means of non-probability sampling with quotas techniques. Results: The test results analysis using the Wilcoxon test marked ratings obtained asymp. Sing (2-tailed) for the effect of hot compress is (0.004) with the a = 0.05 it can be concluded that Ho is rejected Ha accepted. There is the effect of hot compresses to reduce pain active phase of the first stage of labor.